Evaluation of early single dose vaccination on swine influenza A virus transmission in piglets: From experimental data to mechanistic modelling. Issue 19 (5th May 2023) - Andraud, M.; Hervé, S.; Gorin, S.; Barbier, N.; Quéguiner, S.; Paboeuf, F.; Simon, G.; Rose, N.
Highlights: We evaluated swine influenza A transmission virus in piglets with different MDA statuses after a single-dose vaccination. The transmission rate of the challenge strain was found 3.6 time greater in MDA-positive than in MDA-negative pigs. Estimated parameters were unsed to feed a mechanistic model of SwIAV transmission in a farrow-to-finish pig farm. An extended SwIAV within-farm persistence was observed when both sows and piglets were batch-to-batch vaccinated. Alternative vaccination schemes need to be tested, accounting for population dynamics and hosts' immune statuses. Abstract: Swine influenza A virus (swIAV) is a major pathogen affecting pigs with a huge economic impact and potentially zoonotic. Epidemiological studies in endemically infected farms permitted to identify critical factors favoring on-farm persistence, among which maternally-derived antibodies (MDAs). Vaccination is commonly practiced in breeding herds and might be used for immunization of growing pigs at weaning. Althoughinterference between MDAs and vaccination was reported in young piglets, its impact on swIAV transmission was not yet quantified. To this aim, this study reports on a transmission experiment in piglets with or without MDAs, vaccinated with a single dose injection at four weeks of age, and challenged 17 days post-vaccination. To transpose small-scale experiments to real-life situation, estimated parameters were used in a simulation tool to assess their influence at the herd level. Based on a thorough follow-up of the infection chain during the experiment, the transmission of the swIAV challenge strain was highly dependent on the MDA status of the pigs when vaccinated. MDA-positive vaccinated animals showed a direct transmission rate 3.6-fold higher than the one obtained in vaccinated animals without MDAs, estimated to 1.2. Vaccination nevertheless reduced significantly the contribution of airborne transmission when compared with previous estimates obtained in unvaccinated animals. The integration of parameter estimates in a large-scale simulation model, representing a typical farrow-to-finish pig herd, evidenced an extended persistence of viral spread when vaccination of sows and single dose vaccination of piglets was hypothesized. When extinction was quasi-systematic at year 5 post-introduction in the absence of sow vaccination but with single dose early vaccination of piglets, the extinction probability fell down to 33% when batch-to-batch vaccination was implemented both in breeding herd and weaned piglets. These results shed light on a potential adverse effect of single dose vaccination in MDA-positive piglets, which might lead to longer persistence of the SwIAV at the herd level.